Laurel’s Depression in the Novel Love Letters by Ava Dellaira - Islam, Fajar; Maca, Sudirman; Asyrafunnisa, Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2023)
A person's mental condition played a crucial role in shaping their overall well-being and influenced multiple aspects of their life. The study aimed to provide insights into the complex experiences of individuals dealing with depression, enhancing our understanding of mental health. Focusing on the character Laurel in Love Letters to the Dead, the research explored depression symptoms, factors, and coping mechanisms. Data was obtained by repeatedly reading the novel, taking notes, and then categorizing data related to this study. The results of this study show that the factors contributing to Laurel's depression were categorized into two main categories they were: firstly, a stressful environment and life events, and secondly, psychological vulnerability. Laurel also exhibited depression symptoms, including emotional, cognitive, motivational, and physical depression symptoms. Laurel used four types of the defense mechanisms they were repression, displacement, reaction formation, and sublimation to cope her depressive disorder.